Conocimiento de la diabetes mellitus y su relación con el autocuidado en pacientes diabéticos tipo 2 atendidos en el Hospital Isidro Ayora y en el Hospital Manuel Ygnacio Montero. - Díaz Peña, Katerine Cecivel (2013)
Diabetes mellitus is a group of metabolic disorders, affecting various organs and tissues, and is characterized by hyperglycemia. In Ecuador there is a large number of diabetic patients for this reason the aim of this research was to determine the level of knowledge of diabetes mellitus and its relation to self-care in type 2 diabetic patients treated at the Hospital Isidro Ayora and Hospital Manuel Ygnacio Montero. This study is descriptive and cross-sectional survey was applied to 103 randomly selected patients. The results showed that 47.8 % of respondents are in an age range of 45-55 years, showed that 62.1 % do not know about their disease, 40.8 % do not know the complications caused by this disease and only 36.9 % have knowledge about measures of foot care. Using the information collected, it was concluded that most patients have inadequate knowledge about their disease, this is due to misinformation and the lack of importance that these patients will provide the same. Keywords: Diabetes Mellitus, Self-care, complications.